WEST JAVA DECENTRALIZATION AND GOVERNMENT CAPACITY FOR HUMAN RESOURCE DEVELOPMENT - Martin Martin (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
This study aims to explain the relationship between decentralization and human resource development through intermediary government capacity that determines the success of development after decentralization. The results of the study show that decentralization has been implemented well, but there are side effects in the form of money politics and dynasties in political decentralization, the lack of regions that achieve independence in fiscal decentralization, and the low quality of employees due to employee recruitment which is still not optimal in administrative decentralization. The capacity of the national government is only the distributive capacity and horizontal cooperation which can be categorized as good, the capacity of the regional government is only the capacity for horizontal cooperation within one regional government which is included in the good category.